The Origins of Megalithism in Western Iberia: resilient signs of a symbolic revolution? - Diniz, Mariana (2019)
The long-term debate on the rise of Megalithism have been mainly concern with chronological and geographic issues. In archaeological literature, when and where were major questions relying the causes for such a complex symbolic phenomenon as a secondary item. After Oriental missionaries and Segmentary societies explanations fall out Environmental changes have recently been pointed out as a trigger for Megalithism. This vast array of explanations reflect how difficulty is to identify the historical reasons laying beyond such a wide phenomenon were global and local features are combine in a multitude of ways. Creation, mimic, transfers and adaptations are social mechanisms that underlie Megalithism and for each one of this scenarios different reasons could be invoke to explain its origins. In this text, the origins of Megalithism in western Iberia – particularly in southern Portugal – will be discuss testing the traditional materialist perspectives – either Marxist or Processual that considered innovative ideological manifestations as the output of changes in a particular economic infrastructure or subsystem – against Middle Neolithic data. Under those traditional paradigms signs of economic variations that can explain the emergence of Megalithism as significant changes in faunal/botanic assemblages and settlement patterns were search for. Considering the archaeographic absence for an economic turnover the origins of Megalithism seems – in Western Iberia - the result of a symbolic revolution entailed by Middle Neolithic groups and for the moment devoid of a visible economic ingredient. In southern Portugal, the origins of Megalithism – dated c. 3600 BC – are not connected neither to the Neolithisation process – c. two millennia earlier– neither to the Secondary Products Revolution – c. 300/400 hundred years after. By the middle of the 4th millennium BC in a scenario of an apparent economic continuity this symbolic disruption described as Megalithism will emerge. The origins of this innovative symbolic landscapes will be here discuss. KEY WORDS: Megalithism; Origins; Western Iberia; Middle Neolithic, Symbolic revolution